Flexural toughness of SFRC made with fibres extracted from tyres - Tlemat, Houssam; Pilakoutas, Kypros; Neocleous, Kyriacos (My University, 2003)
It has been demonstrated recently that steel fibres extracted from used tyres can be used to reinforce concrete. These fibres have different formats depending on the process used for tyre reduction. The main problem to be avoided is that of fibre balling during mixing. This paper presents the characteristics of four concrete mixes reinforced with three different types of fibres. Particular attention is paid to the flexural toughness of the concrete, and American and Japanese standards are reviewed and compared. It is demonstrated that suitably designed concrete reinforced with steel fibres, extracted from used tyres, can have extremely high toughness.
Keywords: Fibre reinforced concrete; Recycled steel fibres; SFRC; Used tyres fibres